CD73 is a major regulator of adenosinergic signalling in mouse brain. - Natalia Kulesskaya (Public Library of Science (PLoS), 2013)
CD73 (ecto-5'-nucleotidase) is a cell surface enzyme that regulates purinergic signalling by desphosphorylating extracellular AMP to adenosine. 5'-nucleotidases are known to be expressed in brain, but the expression of CD73 and its putative physiological functions at this location remain elusive. Here we found, using immunohistochemistry of wild-type and CD73 deficient mice, that CD73 is prominently expressed in the basal ganglia core comprised of striatum (caudate nucleus and putamen) and globus pallidus. Furthermore, meninges and the olfactory tubercle were found to specifically express CD73. Analysis of wild type (wt) and CD73 deficient mice revealed that CD73 confers the majority of 5'-nucleotidase activity in several areas of the brain. In a battery of behavioural tests and in IntelliCage studies, the CD73 deficient mice demonstrated significantly enhanced exploratory locomotor activity, which probably reflects the prominent expression of CD73 in striatum and globus pallidus that are known to control locomotion. Furthermore, the CD73 deficient mice displayed altered social behaviour. Overall, our data provide a novel mechanistic insight into adenosinergic signalling in brain, which is implicated in the regulation of normal and pathological behaviour.